Study on optimal structure of low power microheater to remain stability at high temperature - Lim, Woonhyun; Kondalkar, Vijay; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2019)
- Microheaters with different structures were fabricated and compared to find an optimal configuration enhancing the performances of C 2 H 2 gas sensor. Three temperature sensors were integrated on the surface of the insulation layer over the microheater, and resistance changes were observed to check the generated heat from the microheater. A low operating voltage of 1mV was applied to the temperature sensor to minimize any influence of thermal heat from the resistance type temperature sensor, whereas high voltages in the range between 10 and 20V were applied to the microheater. A microheater structure generating maximum heat at low voltage was determined. The generated heat was verified by the temperature sensors on the top of the Si 3 N 4 and infrared camera. A long term stability and accuracy of the microheater were observed. The developed microheater was applied to enhance the performances of C 2 H 2 gas sensor and successfully confirmed that the developed microheater greatly contributes to the improvement of sensitivity and selectivity of gas sensor.
Keywords: Different structure; Infra-red cameras; Insulation layers; Long term stability; Low operating voltage; Microheater; Optimal structures; Resistance change; C2H2 sensor; Joule heating; Microheater; Temperature sensor; Thermal conductivity